LACCASE: A ROBUST ENZYME FOR BIOTECHNOLOGICAL ADVANCEMENT - Shehu , Aisha Abbas; Hamisu, Afiya; Umar, Fatima Farouk; Mahmud, Zainab Muhammad (FUDMA Journal of Sciences, 2025)
Laccase, a highly adaptable and resilient enzyme, has become a crucial component in various biotechnological applications due to its remarkable catalytic capabilities and ability to interact with a wide range of substrates. This enzyme's versatility has led to its utilization in numerous processes, including the cleanup of pollutants through bioremediation, the production of biofuels, food processing, and innovative biomedical applications. A comprehensive examination of laccase reveals its unique molecular properties, diverse sources, and classification, as well as its significant roles in different industries. Furthermore, recent advancements and potential future directions in laccase research highlight its vast potential to propel sustainable biotechnological innovations. By harnessing the power of laccase, researchers and industries can develop more efficient and environmentally friendly solutions. As a vital enzyme in modern biotechnology, laccase is poised to transform various fields and contribute to a more sustainable future. Its potential applications are vast, and continued research and development are expected to unlock new opportunities for this enzyme. With its impressive capabilities and broad range of applications, laccase is an enzyme that holds significant promise for driving positive change in various industries and shaping a greener future.
Keywords: Laccase; Biotechnology; Biocatalysis; Sustainable technology; Organic synthesis